The Innovation Process in Emerging Economies: An Effectuation Perspective. (February 2015) - Lingelbach, David; Sriram, Ven; Mersha, Tigineh; Saffu, Kojo
The authors investigate the impact of two contrasting logics, effectuation and causation, on the innovation process in emerging economies (EEs). Effectuation theory, which emphasizes responses to uncertainty, is integrated with the innovation process literature, which emphasizes resource constraints. In particular, the authors show that in EEs the flexibility dimension of effectuation is underemphasized, while its pre-commitment dimension is overemphasized. The combination of effectuation and causation mechanisms is influenced by the industry context, as well as by the type, degree and timing of resource constraints. Employing longitudinal data from six innovation process cases across one industry (financial services) and four EEs (Botswana, Ethiopia, Ghana and South Africa), the authors employ a process approach using real-world data to support their propositions.